Demographic Predictors of Parenting Self-Efficacy Public Elementary School - John Mark Asio (Journal of Elementary and Secondary School, 2025)
Parenting self-efficacy (PSE) refers to the idea and ability to progressively enhance a child’s development and educational outcomes. It is crucial because it directly impacts a child’s academic performance, behavior, and overall well-being. Thus, the main objective of this study was to explore parents’ parenting self-efficacy in a selected public school in a province in the Philippines. The investigator employed a cross-sectional research design and collected data using a standardized instrument among 130 volunteer respondents. The collected data were analyzed by descriptive and inferential statistics using SPSS 23. The result revealed that based on the demographics, most respondents have 2-3 children, were married, unemployed, high school graduates, and had a monthly household income of 5001–10,000 pesos. For parenting self-efficacy (PSE), four constructs garnered a response of "always." Conversely, when engaging in play and facilitating routines, respondents gave an "almost always" response. Inferential statistics also revealed that there was only a significant difference in engaging in play, facilitating routines, and establishing discipline strategies when the study grouped the respondents according to the number of children at home. Lastly, the monthly household income of the parents emerged as the only demographic predictor of parenting self-efficacy (PSE) based on the study results. In conclusion, the PSE of the respondents seemed high enough and was practiced by most of the parents. Only monthly household income generated sufficient results to predict PSE by parents.